ANALYSIS OF THE ECONOMIC POTENTIAL OF THE MANUFACTURING INDUSTRY SECTOR IN SUMATERA BARAT PROVINCE (Economic Education Faculty of Economics and Business Universitas PGRI Sumatera Barat, 2021)
This study aims to determine which sub-sectors have the potential and advantages of each regency/municipality in West Sumatra using LQ and shift share analysis. The results of the LQ and shift share analysis obtained 4 regional groups, namely the first group there is 11 region that has fast manufacturing growth; the second group, there is 3 region that has deep growth in the manufacturing but still has the potential to be developed; the third group is 1 municipality which has deep growth but developing industrial sector growth; the fourth group has 4 region depressed regions with weak competitiveness and also the contribution of the province of West Sumatra is low. From the results of the two analyzes, the government can focus more on providing guidance to manufacturing entrepreneurs, including those in potential, developing, and depressed regions.